Exosomes in Sepsis - Murao, Atsushi; Brenner, Max; Aziz, Monowar; Wang, Ping (Frontiers in Immunology, 2020)
Sepsis is a severe state of infection with high mortality. Pathogen-associated molecular patterns and damage-associated molecular patterns (DAMPs) initiate dysregulated systemic inflammation upon binding to pattern recognition receptors. Exosomes are endosome-derived vesicles, which carry proteins, lipids and nucleic acids, and facilitate intercellular communications. Studies have shown altered contents and function of exosomes during sepsis. In sepsis, exosomes carry in-creased levels of cytokines and DAMPs to induce inflammation. Exosomal DAMPs include, but are not limited to, high mobility group box 1, heat shock proteins, histones, adenosine triphos-phate, and extracellular RNA. Exosomes released during sepsis have impact on multiple organs, including the lungs, kidneys, liver, cardiovascular system, and central nervous system. Here, we review the mechanisms of inflammation caused by exosomes, and their contribution to multiple organ dysfunction in sepsis.